1996
DOI: 10.1177/019262339602400211
|View full text |Cite
|
Sign up to set email alerts
|

Lipidosis Induced in the Dog Gallbladder by a Direct 5-Lipoxygenase Inhibitor

Abstract: The direct 5-lipoxygenase inhibitor L-739,010

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…While L-739,010 caused a dose-dependent elevation in alanine transaminase levels in dogs, suggesting that it induced hepatotoxicity, 116 histopathological analysis showed no indication of liver toxicity. 117 It initiated lipidosis in the gall bladder. 117 Binding of L-739,010 to proteins requires metabolism.…”
Section: -Substituted Furansmentioning
confidence: 99%
See 1 more Smart Citation
“…While L-739,010 caused a dose-dependent elevation in alanine transaminase levels in dogs, suggesting that it induced hepatotoxicity, 116 histopathological analysis showed no indication of liver toxicity. 117 It initiated lipidosis in the gall bladder. 117 Binding of L-739,010 to proteins requires metabolism.…”
Section: -Substituted Furansmentioning
confidence: 99%
“…117 It initiated lipidosis in the gall bladder. 117 Binding of L-739,010 to proteins requires metabolism. Incubation of L-739,010 with liver microsomes results in the NADPHdependent loss of the parent compound without significant formation of detectable metabolites.…”
Section: -Substituted Furansmentioning
confidence: 99%
“…Microsomal metabolism studies on L-739,010have revealed the formation of reactive intermediates at both the dioxabicyclooctanyl group and the furan ring . (b) In preclinical animal toxicity studies, 3g has shown induction of lipidosis in the dog gallbladder …”
Section: Referencesmentioning
confidence: 99%
“…Future studies designed to examine changes in the plasma lipidome and gallbladder lipid over the course of mucocele development may shed further light on this relationship. Prior descriptions of the ultrastructural appearance of canine gallbladder epithelium are infrequent [18,[28][29][30] but include a toxicology study reporting gallbladder epithelial lipidosis in dogs treated with an inhibitor of leukotriene…”
Section: Plos Onementioning
confidence: 99%